2015
DOI: 10.1002/ece3.1741
|View full text |Cite
|
Sign up to set email alerts
|

Swimming through sand: connectivity of aquatic fauna in deserts

Abstract: Freshwater ecosystems in arid regions range from highly fragmented to highly connected, and connectivity has been assumed to be a major factor in the persistence of aquatic biota in arid environments. This review sought to synthesize existing research on genetic estimation of population connectivity in desert freshwaters, identify knowledge gaps, and set priorities for future studies of connectivity in these environments. From an extensive literature search, we synthesized the approaches applied, systems studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 76 publications
(138 reference statements)
4
20
0
Order By: Relevance
“…A study by Bogan et al () found that macrohabitat type was more important than geographic location in structuring aquatic invertebrate communities in the Sonoran Desert. Alternatively, previous studies have shown that local environmental conditions in desert springs may not be useful predictors of macroinvertebrate community composition (Rader et al, ; Sada, Fleishman, & Murphy, ), and that connectivity among spring systems may be a better predictor of species turnover than abiotic parameters (Murphy, Pavlova, Thompson, Davis, & Sunnucks, ). Despite differences in physicochemical conditions among spring sites, results from this study suggest that geographic distance is the most influential factor in community composition among springs in the Chihuahuan Desert.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Bogan et al () found that macrohabitat type was more important than geographic location in structuring aquatic invertebrate communities in the Sonoran Desert. Alternatively, previous studies have shown that local environmental conditions in desert springs may not be useful predictors of macroinvertebrate community composition (Rader et al, ; Sada, Fleishman, & Murphy, ), and that connectivity among spring systems may be a better predictor of species turnover than abiotic parameters (Murphy, Pavlova, Thompson, Davis, & Sunnucks, ). Despite differences in physicochemical conditions among spring sites, results from this study suggest that geographic distance is the most influential factor in community composition among springs in the Chihuahuan Desert.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the species' reproductive biology may have facilitated expansion into new habitats and gene flow among populations, but more recently, and in far more arid conditions, populations have very little gene flow among them. Once individual spring populations become extirpated, higher levels of fragmentation and genetic isolation/structure result, a common pattern in desert freshwater taxa (Murphy et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Extreme events like large‐scale floods, which are set to play an increasingly strong role in river ecosystems (Woodward et al., ), may override many of these dispersal constraints that network‐constrained dispersers face. Extreme flood events may increase connectivity, leading to movement of organisms between locations that would not occur under baseflow conditions, particularly in arid systems (Murphy, Pavlova, Thompson, Davis, & Sunnucks, ). Mossop et al.…”
Section: What Factors Influence Dispersal In Riverine Metacommunities?mentioning
confidence: 99%